Behaviour of fly ash geopolymer containing fillers and fibres at elevated temperatures and its application as fire resistant coating for timber - Haque, Sharany (Curtin University, 2017)
Geopolymer has gained its focus recently and are generally believed to have good fire resistance due to their ceramic-like properties. As timber structures are very much popular around the globe and this structure is also very vulnerable to fire so this geopolymer coating can be used to protect the timber from fire to some extent. This research evaluated the effectiveness of fly ash based geopolymer coating to protect the damage of timber against fire.